Application of low dose aspirin in pre-eclampsia - Ren, Yu; Zhao, Yong; Yang, Xiangdong; Shen, Chaojun; Luo, Hua (Frontiers in Medicine, 2023)
As an antiplatelet drug, aspirin is widely used in the primary and secondary prevention of cardiovascular and cerebrovascular diseases. Low-dose aspirin is also widely used to prevent pre-eclampsia and fetal growth retardation in utero. However, the use of aspirin during pregnancy is controversial. Since 1985, when aspirin was reported to be effective in obstetric, numerous studies have attempted to determine the effect of low-dose aspirin on the morbidity of pre-eclampsia, but have remained inconclusive. Guidelines for aspirin in the prevention of pre-eclampsia is different in different countries and regions. This article summarizes the research progress, mechanism and application prospect of aspirin in the prevention of pre-eclampsia, in order to provide a theoretical basis for the rational use of aspirin in pregnancy.